Trans-arterial chemoembolization (TACE) in patients with unresectable Hepatocellular carcinoma: Experience from a tertiary care centre in India - Paul, Shashi Bala; Gamanagatti, Shivanand; Sreenivas, Vishnubhatla; Chandrashekhara, Sheragaru Hanumanthappa; Mukund, Amar; Gulati, Manpreet Singh; Gupta, Arun Kumar; Acharya, Subrat Kumar (Indian Journal of Radiology and Imaging, 2011)
Aims: To evaluate the outcome following transarterial chemoembolization (TACE) and to identify the predictors of survival in patients with unresectable hepatocellular carcinoma (HCC). Material and Methods: HCC patients reporting to our hospital (2001-2007) were subjected to clinical, biochemical, and radiological examination. TACE was performed in those who fulfilled the inclusion criteria. Follow-up assessment was done with multiphase CT scan of the liver at 1, 3, and 6 months. Tumor response and survival rate were estimated. Univariate and multivariate analyses were done for determinants of survival. Results: A total of 73 patients (69 males, 4 females; mean age 49±13.4 years) were subjected to 123 sessions of TACE. The Child′s classification was: A - 56 patients and B - 17 patients. Barcelona Clinic staging was: A - 20 patients, B - 38 patients, and C - 15 patients. Tumor size was ≤5cm in 28 (38%) patients, >5-10 cm in 28 (38%) patients, and >10 cm in 17 (23%) patients. Median follow-up was for 12 months (range: 1-77 months). No significant postprocedure complications were encountered. Overall survival rate was 66%, 47%, and 36.4% at 1, 2, and 3 years, respectively. Tumor size emerged as an important predictor of survival. Conclusion: TACE offers a reasonable palliative therapy for HCC. Initial tumor size is an independent predictor of survival.
Keywords: Hepatocellular carcinoma; survival rate; transarterial chemoembolisation